PERSONALITY TRAITS AND ITS IMPACT ON FINANCIAL INCLUSION: A STUDY AMONG THE SCHEDULED TRIBES - RAMANUJAM, Veluchamy; DHANYAMOL, Valiplackal Raveendran; LINGARAJA, Kasilingam; AISWARRYA, Elangovan (International Journal of Psychosocial Rehabilitation, 2020)
Financial inclusion is gaining momentum both as a concept and as a policy solution, and, while it can do some good, it is not likely to change the economic fate of the world’s poor. Regardless of this, given the recent attention it is receiving, we ought to understand it and assess its feasibility and merit. Given that banks in India claimed successful comprehensive financial inclusion, we aimed to study the breadth and depth of financial inclusion in South India, and this study sheds light on the validity of claims of financial reach and breadth. Further, since the mere opening of bank accounts is not sufficient for inclusive growth, the study identifies the accessing of savings, credit and other financial services. Since the present study has made an attempt to explain the profile of the Scheduled Tribes in financial inclusion, their level of financial inclusion, the present study includes the analyzing and the interoperating the profiles, levels of financial inclusion and the factors affecting the access of financial inclusion of the Scheduled Tribes in Kerala. In this study is attempt to analysis the association between the various factors among the financial inclusion and to check the reliability and validity among factors that can be affect the financial inclusion among the scheduled trines in Kerala. The analysis of financial inclusion conclude that the level of perception on various service quality factors are not up to their level of expectation among the rural Scheduled Tribes than among the urban Scheduled Tribes.